The miR-124-3p/Neuropilin-1 Axis Contributes to the Proliferation and Metastasis of Triple-Negative Breast Cancer Cells and Co-Activates the TGF-β Pathway - Zhang, Jiayang; Zhang, Xuesong; Li, Ziyi; Wang, Qingshan; Shi, Yan; Jiang, Xian; Sun, Xueying (Frontiers in Oncology, 2021)
Triple-negative breast cancer (TNBC) accounts for 90% of breast cancer-associated mortality. Neuropilin-1 (NRP-1) acts as a non-tyrosine kinase receptor for several cellular signaling pathways involved in the proliferation and metastasis of cancer cells. However, the miRNAs that regulate NRP-1 expression and the underlying mechanisms in TNBC cells remain unclear. In the present study, we found that TNBC cells expressed higher levels of NRP-1 than non-TNBC cells. Stable transfectants depleted of NRP-1 were generated from two TNBC cell lines, human MDA-MB-231 and mouse 4T1 cells. NRP-1 depletion significantly suppressed the proliferation of TNBC cells by arresting the cell cycle at phase G0/G1 by upregulating p27 and downregulating cyclin E and cyclin-dependent kinase 2. NRP-1 depletion also repressed cell migration and epithelial-mesenchymal transition (EMT) by inducing the upregulation of E-cadherin and the downregulation of N-cadherin, matrix metalloproteinase (MMP)-2 and MMP-9, and reducing MMP-2 and MMP-9 activities as detected by gelatin zymography assay. By applying multiple miRNA-target prediction tools, we screened potential miRNAs with binding sites with the 3’-untranslated region of the NRP-1 gene and selected 12 miRNA candidates, among which miR-124-3p displayed the most vigorous activity to downregulate NRP-1 as validated by luciferase assay and miRNA transfection assay. By downregulating NRP-1, miR-124-3p mimics inhibited the proliferation, migration, and invasion of TNBC cells, and antagomiR-124-3p could partially abolish the effects of NRP-1 depletion. In the animal experiments, NRP-1 depletion inhibited tumorigenesis and liver metastasis of TNBC cells, while miR-124-3p mimics inhibited the growth of established TNBC tumors. In the mechanistic exploration, we revealed that NRP-1 co-interacted with transforming growth factor (TGF)-beta to activate the TGF-beta pathway, which regulates EMT-related molecules. In summary, the present results indicate that the miR-124-3p/NRP-1 axis contributes to the proliferation and metastasis of TNBC cells and co-activates the TGF-β pathway, suggesting that these molecules may present as potential therapeutic targets and valuable biomarkers for TNBC.